Climate and COVID 19: the relation between air temperature, solar radiation and new daily cases in Ponta Grossa, PR, Brazil (Terr@ Plural, 2022)
The world is experiencing a moment of apprehension, which began in late2019 and extended throughout the years 2020/21 which corresponds to the pandemicperiod of Covid 19. The disease arrived in Brazil in late February and spread allover the country. In Ponta Grossa, it arrived a few months later and the first case ofcommunity transmission occurred on 05/26/2020. From this date on, it was possible toestablish correlations between the climate and Covid 19, considering air temperature(maximum, average, and minimum) and solar radiation, the main goal of this paper.With the elaboration of graphs and statistical treatment of the data, it was possible todetermine the correlation between climatic variables and the new cases of Covid 19. Itshould be noted that it is necessary to continue the research to better understand themoment we are living and the mentioned relationships.
Keywords: Pandemia; Coronavirus; urban climate; climate variables